The Integration-Interconnection Paradigm in Islamic Law: Al-Syatibi’s Thought in Al-Muwafaqat - Mashduqi, Muhammad Anis (UIN Sunan Kalijaga Yogyakarta, 2024)
The study of Islamic law has tend to focus on the textual approach and often neglects its interaction with rational sciences. Al-Syatibi’s thought in Al-Muwafaqat offers a new paradigm that combines textual analysis with social reality through the maqasid al-shari’ah approach. However, previous academic studies have not specifically explored how Al-Syatibi’s ideas can be a methodological foundation for the integration-interconnection paradigm. This research uses a text analysis method with a historical-critical and contextual approach to Al-Muwafaqat and related literature. The data is analyzed to understand the relationship between textual and rational epistemology in the study of Islamic law. Al-Syatibi emphasized the importance of the rational-empirical approach in the investigation of Islamic jurisprudence. According to him, the study of Islamic law must involve textual methodology (al-ijtihad fi al-nash) and rational-empirical methodology (al-ijtihad fi al-waqi’). The idea expressed by Al-Syatibi can be interpreted as legitimizing the importance of an integrated and interconnected paradigm in Islamic studies, which includes the field of Islamic law. This study emphasizes that integrating social science, economics, and science in the analysis of Islamic law can answer epistemological and contextual challenges. Kajian hukum Islam selama ini cenderung terfokus pada pendekatan tekstual dan sering diabaikan integrasinya dengan ilmu-ilmu rasional. Pemikiran Al-Syatibi dalam Al-Muwafaqat menawarkan paradigma baru yang menggabungkan analisis teks dengan realitas sosial melalui pendekatan maqasid al-shari’ah. Namun, kajian akademik sebelumnya belum secara spesifik mengeksplorasi bagaimana gagasan Al-Syatibi dapat menjadi landasan metodologis untuk paradigma integrasi-interkoneksi. Penelitian ini menggunakan metode analisis teks dengan pendekatan historis-kritis dan kontekstual terhadap Al-Muwafaqat serta literatur terkait. Data dianalisis untuk memahami hubungan antara epistemologi tekstual dan rasional dalam studi hukum Islam. Al-Syatibi menekankan pentingnya pendekatan rasional-empiris dalam penyelidikan yurisprudensi Islam. Menurutnya, studi hukum Islam harus melibatkan metodologi tekstual (al-ijtihad fi al-nash) dan metodologi rasional-empiris (al-ijtihad fi al-waqi’). Gagasan yang diungkapkan oleh Al-Syatibi dapat diartikan sebagai legitimasi pentingnya paradigma yang terintegrasi dan terinterkoneksi dalam studi Islam, yang meliputi bidang hukum Islam. Studi ini menekankan bahwa pengintegrasian ilmu sosial, ekonomi, dan sains dalam analisis hukum Islam dapat menjawab tantangan epistemologis dan kontekstual.